AB INITIO MODELING AND NANOSTRUCTURING OF TIC SURFACE BY LASER RADIATION - V. V. Ilyasov; D. K. Pham (Advanced Engineering Research)
The processes of surface nanostructuring of titanium carbide by Nd radiation: YAG-laser with the wavelength of 1.06 microns is investigated. The laser pulse length is 40 ns, the travel rate is 10 mm / s. The radiation energy density on the surface of titanium carbide at the oscillation frequency of 2000 Hz is 2.06 ÷ 6.36 J / cm2. The results of ab initio study of the atomic, electronic structure, and the elastic characteristics of TiC and TiC1-хOх (x = 0,25; 0,5; 0,75) are presented. The band structure of TiC calculated with the use of the density functional theory corresponds to a metal type. It is shown that the calculated elastic properties of titanium carbide are in good agreement with the known theoretical and experimental estimates. The study of the microstructures topography on the of titanium carbide surface using the atomic force microscopy (AFM) shows that in the area of the direct laser action, the roughness is 0.254 µm. Mechanical properties in the direct laser impingement spots, and in the temperature exposure regions are investigated by the nanoindentation. The effect of nanostructuring is determined: the titanium carbide surface hardness goes up to 47.2 hPa after the laser action.